Corporate social responsibility and sustainability emerging trends in developing economies - Eweje, Gabriel (Emerald, 2014)
There is growing public interest and concern regarding the sustainability of communities. This volume offers a critical review of current trends around Corporate social responsibility (CSR) and sustainability activities in developing and emerging economies. The book makes three main contributions. First, it argues that while CSR and sustainability are global concerns, they are embedded in institutional contexts. Second, it suggests that these are not merely business issues; other stakeholders can and should play an important role in societal and environmental sustainability and development. Third, CSR and sustainability are not isolated from business and can be integrated in business strategy and corporate governance structures. The book offers a conceptual paradigm and empirical evidence as to how businesses and other stakeholders in developing and emerging economies can ensure their activities make a positive contribution to the communities and countries in which they operate. With topical and current issues discussed, it is a must have for business practitioners, policy makers, experts in supranational organizations, academics and students.
Keywords: Social responsibility of business -- Developing countries.; Sustainable development -- Developing countries.; elektronické knihy; electronic books